Factors Affecting the Standard of Life of Asnaf Under Asnaf Care Program Masjid Lama Permatang Badak, Kuantan - Mohamad Hilmi, Mat Said; Noryanti, Muhammad; Norsuhaila, Musa; Nabila, Abdul Malek (EasyChair, 2023)
Post-covid has seen changes in the standard of living of the community due to the effects of covid that hit Malaysia for about 2 years. The researcher was called to study the factors that affect the standard of living of asnaf under the asnaf caring program of the Masjid Lama Permatang Badak (MLPB), Kuantan Pahang. This study aims to see to what extent the factors that lead to poverty mentioned in Kitab al-Adab written by Al-Habib Zain Bin Ibrahim correspond to the situation of asnaf itself. Through the book, page 324, no. 34, titled Adab Ketika Dalam Keadaan Miskin dan Kaya (Manners When Poor and Rich) under the sub-topic "Adab Ketika Dalam Keadaan Miskin (Manners When Poor)" which lists 14 factors that can lead to poverty, is the list of 14 factors found in the Asnaf zakat MLPB or vice versa. For the purpose of this study, the researcher has tried to build an instrument in the form of a questionnaire prepared from the 14 factors stated in the Book. This preliminary study was conducted on 30 asnaf selected to fill out the questionnaire. The results of the developed questionnaire found that 14 factors that lead to poverty have a basis. However, due to the processing of the questionnaire which is still at an early stage and the form-filling method by the asnaf is not perfect, the researcher found that the findings of this study can still be improved. The suggested improvements are better processing or updating of questionnaires, a larger number of asnaf participants and methods or guidelines for filling out questionnaires by asnaf that are more thorough and customer-friendly.